2017
DOI: 10.1002/ajpa.23308
|View full text |Cite
|
Sign up to set email alerts
|

A female Viking warrior confirmed by genomics

Abstract: ObjectivesThe objective of this study has been to confirm the sex and the affinity of an individual buried in a well‐furnished warrior grave (Bj 581) in the Viking Age town of Birka, Sweden. Previously, based on the material and historical records, the male sex has been associated with the gender of the warrior and such was the case with Bj 581. An earlier osteological classification of the individual as female was considered controversial in a historical and archaeological context. A genomic confirmation of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
51
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(59 citation statements)
references
References 46 publications
2
51
0
1
Order By: Relevance
“…Many of the visual methods used in forensic anthropology are acknowledged to be subjective in nature, and have a general reliance upon observation and the specialized experience of the observer (e.g., Grivas and Komar (12)). It is important to note that contrary to the letter (1) that implies that experience and practicing experts are immune to bias, a recent study by Hederstierna-Jonson et al (13) shows that sex estimation of human remains appeared to be influenced by items associated with the remains ("warrior equipment") and prior understandings of the cultural traditions of that time period. The authors of that study go as far to conclude that their findings signal that "great caution against sweeping interpretations based on archaeological context and preconceptions" (13) should be taken.…”
Section: The Potential Effects Of Initial Exposure To Context At a Crmentioning
confidence: 87%
“…Many of the visual methods used in forensic anthropology are acknowledged to be subjective in nature, and have a general reliance upon observation and the specialized experience of the observer (e.g., Grivas and Komar (12)). It is important to note that contrary to the letter (1) that implies that experience and practicing experts are immune to bias, a recent study by Hederstierna-Jonson et al (13) shows that sex estimation of human remains appeared to be influenced by items associated with the remains ("warrior equipment") and prior understandings of the cultural traditions of that time period. The authors of that study go as far to conclude that their findings signal that "great caution against sweeping interpretations based on archaeological context and preconceptions" (13) should be taken.…”
Section: The Potential Effects Of Initial Exposure To Context At a Crmentioning
confidence: 87%
“…On 7 September 2017, an article with the title 'A female Viking warrior confirmed by genomics' was published in American Journal of Physical Anthropology (Hedenstierna-Jonson et al 2017). The article presented the results from DNA and strontium isotope analyses of samples from a human skeleton uncovered in 1878, along with two horses and the typical equipment of a warrior, in grave Bj 581 in the excavations at the Viking Age town of Birka, Sweden.…”
Section: The Birka Warriormentioning
confidence: 99%
“…Then the high-born lady saw them play the wounding game, she resolved on a hard course and flung off her cloak; she took a naked sword and fought for her kinsmen's lives, she was handy at fighting, wherever she aimed her blows. (Larrington 1996, in Hedenstierna-Jonson et al 2017.…”
Section: The Birka Warriormentioning
confidence: 99%
“…In September 2017, the American Journal of Physical Anthropology published an article by the current authors entitled ‘A female Viking warrior confirmed by genomics’ (Hedenstierna-Jonson et al 2017). It presented the results of extensive ancient DNA analysis, following earlier osteological studies.…”
Section: Introductionmentioning
confidence: 99%